ESMO management and treatment adapted recommendations in the COVID-19 era: gynaecological malignancies. (27th July 2020) - Colombo, Ilaria; Zaccarelli, Eleonora; Del Grande, Maria; Tomao, Federica; Multinu, Francesco; Betella, Ilaria; Ledermann, Jonathan A; Gonzalez-Martin, Antonio; Sessa, Cristiana; Colombo, Nicoletta
Abstract : The rapid spread of severe acute respiratory syndrome coronavirus 2 infection and its related disease (COVID-19) has required an immediate and coordinate healthcare response to face the worldwide emergency and define strategies to maintain the continuum of care for the non-COVID-19 diseases while protecting patients and healthcare providers. The dimension of the COVID-19 pandemic poses an unprecedented risk especially for the more vulnerable populations. To manage patients with cancer adequately, maintaining the highest quality of care, a definition of value-based priorities is necessary to define which interventions can be safely postponed without affecting patients' outcome. The European Society for Medical Oncology (ESMO) has endorsed a tiered approach across three different levels of priority (high, medium, low) incorporating information on the value-based prioritisation and clinical cogency of the interventions that can be applied for different disease sites. Patients with gynaecological cancer are at particular risk of COVID-19 complications because of their age and prevalence of comorbidities. The definition of priority level should be based on tumour stage and histology, cancer-related symptoms or complications, aim (curative vs palliative) and magnitude of benefit of the oncological intervention, patients' general condition and preferences. The decision-making process always needs to consider the disease-specific national and international guidelines and the local healthcare system and social resources, and a changing situation in relation to COVID-19 infection. These recommendations aim to provide guidance for the definition of deferrable and undeferrable interventions during the COVID-19 pandemic for ovarian, endometrial and cervical cancers within the context of the ESMO Clinical Practice Guidelines.